Post‐prostate biopsy acute bacterial prostatitis and screening cultures using selective media: An overview. (10th February 2022) - Acosta, Herik; Sadahira, Takuya; Sekito, Takanori; Maruyama, Yuki; Iwata, Takehiro; Araki, Motoo; Ogawa, Kohei; Tsuboi, Ichiro; Wada, Koichiro
Abstract: The development of several culture media and the availability to isolate and treat pathogens prior to a surgical procedure give us the ability to minimize treatment‐related complications, and ultimately results in better outcomes for patients and avoidance of unwanted post‐procedure inpatient admissions. In the last decade, an increasing incidence of multidrug‐resistant Escherichia coli, especially extended‐spectrum beta‐lactamase‐producing E. coli and fluoroquinolone‐resistant pathogens, has been reported. These resistant species frequently colonize the rectal flora and gain access to the systemic circulation via the rectal plexus following a prostate biopsy. The bacteria can eventually lead to life‐threatening complications, which is especially important in high‐risk patients with multiple co‐morbidities. Previously published studies have focused on the isolation of these pathogens with selective media before an invasive procedure and the potential benefits of incorporating the use of selective media as a mandatory pre‐operative step. This preventive measure will allow us to offer a tailored prophylactic treatment that benefits patients and reduces the economic burden for the hospital.